MXene Based Conductive Transparent Films (CTFs) Towards Printed Electronics Applications - Balobaid, Laila Ali; Nicolosi, Valeria; Coleman, Jonathan; Spurling, Dahnan (My University, 2026)
MXene 2D materials attracted researchers due to their unique properties and tuneability ranging from metallic to semiconductor. In particular, Ti3C2Tx became the focus of research efforts lately pertaining to its high conductivity. This work applies liquid-liquid interface deposition (LLID) to synthesize CTFs whilst reporting the measured conductivity for the MXene-based CTFs to be 3.3 x 105 S/m at 11.7 nm thickness.
EuroMAX26
PUBLISHED
Dublin
Keywords: Nanoscience & Materials; Smart & Sustainable Planet; Nanotechnology; Physics; Surface and interface physics